2005
DOI: 10.1136/bjo.2005.072892
|View full text |Cite
|
Sign up to set email alerts
|

Mortality following exenteration for malignant tumours of the orbit

Abstract: Background: Orbital exenteration is a rare, but disfiguring procedure reserved for the treatment of locally invasive malignancy or potentially life threatening orbital neoplasms, when less destructive techniques are inadequate. The authors report their experience and analyses of 64 cases of orbital exenteration performed over a 13 year period, looking specifically at key factors affecting mortality associated with such a destructive surgical procedure. Methods: Records were reviewed retrospectively of all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 17 publications
(12 reference statements)
6
25
3
Order By: Relevance
“…This is lower than the rates of positive permanent margins between 28 and 47% reported in other series. 6,17,19 One possible explanation for this is that the multidisciplinary approach to tumor resection typically used at this tertiary referral cancer center enabled additional surgical procedures to be performed at the same time as the exenteration in order to optimize tumor control. In our series, multivariate analysis showed that the presence of a positive final surgical margin was the only potential factor that was associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is lower than the rates of positive permanent margins between 28 and 47% reported in other series. 6,17,19 One possible explanation for this is that the multidisciplinary approach to tumor resection typically used at this tertiary referral cancer center enabled additional surgical procedures to be performed at the same time as the exenteration in order to optimize tumor control. In our series, multivariate analysis showed that the presence of a positive final surgical margin was the only potential factor that was associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, positive final surgical margins have not been associated with a worse prognosis in other series. 6,17 It may be hard to compare numbers between different retrospective series because of the heterogeneity of inclusion criteria. This is possibly due to lower overall rates of positive margins in this series as mentioned above, as well as higher rate of micrometastasis of other tumor types such as melanoma, malignant sarcomas, adenoid cystic carcinoma, sinonasal tumors, primary orbital tumors, and lacrimal tumors, which were not included in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemotherapy can be performed both before surgery to reduce the tumor size, and after surgery to prevent tumor regrowth. 6,9,19 Surgery is frequently performed to prevent tumor 2,6,20 In this study, no subjects underwent radiotherapy. Doctors often decide to only observe when the tumor mass is still very small, seems unthreatening, and has a probability of spontaneous regression.…”
Section: Discussionmentioning
confidence: 99%